Pengaruh Digitalisasi Spbu Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen - Gumelar, Agung Yedi; Rianto, Toha; Sobar, Agus (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2023)
One of the key elements that might raise customer happiness is the digitalization of gas stations and the quality of their services.  The goal of this study is to ascertain how customer happiness is affected by the digitization of gas stations and service quality.  The data for this study come from 34 petrol stations in Sukabumi City and Regency, which has a population of 100,000. A sample of 383 respondents was obtained using a sampling technique in this study that used a sample size of web.raosoft.com and an error rate of 5%.   Questionnaires are distributed as part of the data collection process. In this work, multiple linear regression analysis was the method of analysis. According to the findings, customer satisfaction increased by 27% as a result of the digitalization of gas stations and the quality of the service, with other factors affecting the remaining 73%. The quality of service, which has a dominant influence of 35.5%, is variable. The study's contribution is to increase the body of knowledge in the field of marketing management about the digitalization of gas stations and service quality in the context of businesses.